Return To Education In Malaysia - Said, R; McNabb, R; Asmaddy Haris (Univ Utara Malaysia Press, 2024)
The aim of this paper is to present a picture of return to education in Malaysia over the period from 1984 to 1997 based on earning equations model. The paper employed a set of data comprising micro-level data from the Household Income Survey (HIS) for several years during the period 1984 to 1997. The main finding of this paper is the changes in the wage differentials favouring the middle level of education (secondary level of education) workers. In general, the results show that the return for each level of qualification declined between 1984 and 1997, especially at the higher levels (diploma and degree). Interestingly, the return to education for females at low levels of education is higher than the return by males. However, at higher levels of qualification, especially for those with secondary and high school qualifications, males traditionally have a higher return compared to females workers. The results also indicated a significant gender differential, however the differences has fallen over time.